Risk Factors for Recurrence after First Seizure - J Gordon Millichap (Pediatric Neurology Briefs, 2004)
Recurrence after a first unprovoked cryptogenic/idiopathic seizure was studied in 213 children followed at FCM-Unicamp, Campinas, SP, Brazil.